Collaborating the Role of Stakeholders in Waste Management - Zainul Ikhwan (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2022)
The main problem of waste management on small islands is that the amount of waste often exceeds the capacity that the island can handle, due to the limited availability of land, volume of land, budget, and human resources. Unmanaged waste generation has an ecological impact such as environmental pollution, loss of natural resources; economic impacts such as decreased productivity; social impacts such as the emergence of conflict, and health impacts uch as increasing the number of environmental-based diseases on the community and the wider environment. The stakeholder role collaboration strategy is needed. This study aims to formulate a collaborative strategy for the role of stakeholders in the proper management of Penyengat Island, Tanjungpinang City. This research method is qualitative. Waste management on the island of Penyengat demands the role of the government, the private sector, and the community. The government moves in terms of regulations, facilities, and implementers. The role of the private sector is more to provide funds and empowerment. While the role of the community is more on empowering efforts to reduce waste and its utilization.